NAOH EFFECT ON BIOCOMPOSITES: STUDI PENGARUH NAOH TERHADAP KEKUATAN TARIK BIOKOMPOSIT BERPENGUAT SERAT ALAM - Elok, Elok Hidayah; Aminatur Rosyidah; Febby Rizka Tamami (JEAS (Journal of Educational and Applied Science), 2024)
Concern for the environment becomes a supporting factor in biocomposite research. Composite materials that previously used synthetic materials need to be swiftly transitioned into biocomposite materials, where one or all of its constituent materials originate from nature, making it more environmentally friendly and capable of being produced in large and sustainable quantities. However, in its application, biocomposite manufacturers still encounter several problems, especially in the field of mechanical strength. When compared to conventional composite materials, the mechanical strength of biocomposites is still lower. One effort that can be made to improve the mechanical strength of biocomposites is by treating natural fibers that will be used as reinforcement in the biocomposite with chemical processes. One easy and effective chemical treatment to apply is alkalinization using NaOH. This article will discuss a number of theories and research results regarding the influence of NaOH on the mechanical characteristics, specifically tensile strength, of natural fiber-reinforced biocomposites. The analysis process is carried out by gathering several reference sources, including books, scientific articles, and nationally and internationally recognized proceedings. All information from reference sources containing information about biocomposites, NaOH, natural fibers, and tensile strength is analyzed and rewritten in the form of an article.